Near infrared organic photodetectors based on enhanced charge transfer state absorption by photonic architectures. Issue 28 (29th June 2020) - Gibert-Roca, Martí; Molet, Pau; Mihi, Agustín; Campoy-Quiles, Mariano
Abstract : Solution processed organic photodetectors with a nanostructured active layer in the shape of a photonic crystal exhibit an improved NIR response, below the band gap of the active layer materials, that can be tuned by varying the lattice parameter. Abstract : Near infrared photodetectors are a widespread and fundamental technology in many disciplines, from astronomy and telecommunications to medical sciences. Current technologies are now striving to include new aspects in this technology such as wearability, flexibility and tunability. Organic photodetectors easily offer many of those advantages but their relatively high bandgaps hinder NIR operation. In this work, we demonstrate solution processed organic photodetectors with improved NIR response thanks to a nanostructured active layer in the shape of a photonic crystal. The latter strongly increases the charge transfer state absorption, which is normally weak but broadband, increasing the optical path of light and resulting in remarkable photoresponse significantly below the band gap of the blend. We show responsivities up to 50 mA W −1 at 900 nm for PBTTT:PC71 BM based photodetectors. On top of that, by varying the lattice parameter of the photonic crystal structure, the spectral response of the photodetectors can be tuned beyond 1000 nm. Furthermore, our photonic structure can be easily implemented in the device in a single nanoimprinting step, with minimal disruption on the fabrication process, which makes this approach very promising for upscaling.